MFGM-enriched whey displays antiviral activity against common pediatric viruses in vitro - Kramer, Evelien; Patil, Ketki; Triantis, Vassilis; Bastiaans, Jan A. H.; Mazzon, Michela; Ramani, Sasirekha; Lambers, Tim T. (Frontiers in Nutrition, 2024)
Background Among the most common mucosal viral infections in infants are rotavirus, one of the main causes of severe gastroenteritis in infants and children up to 5 years, and respiratory syncytial virus (RSV), one of the leading causes of lower respiratory tract infections. Both human milk and bovine milk derived factors may provide protection against mucosal viral infections. More recently, a similar activity of milk derived proteins was suggested for SARS-CoV-2. The goal of the current study was to test antiviral activity of the bovine milkfat globule membrane (MFGM) against rotavirus, RSV and SARS-CoV-2 and to further characterize MFGM-enriched whey to identify which components in MFGM-enriched whey may contribute to the inhibitory activity. Methods The effects of MFGM-enriched whey, its whey protein isolate counterpart (WPI, obtained from the same production process) and a conventional whey protein concentrate (WPC) on rotavirus (strains Wa and SA114F), RSV (strain RSV-A2) and SARS-CoV-2 (Alpha variant) infectivity were determined using MA104 cells, human alveolar basal epithelial (A549) cells and monkey kidney (Vero E6) cells, respectively. The compounds were characterized in detail by LC–MS/MS and 31P-NMR to determine protein and phospholipid composition, respectively. Results Relative to its WPI counterpart, MFGM-enriched whey demonstrated a dose-dependent inhibition for both rotavirus and RSV whereas for SARS-CoV-2 inhibition was only observed at the highest concentration tested. Label-free quantification (LFQ) and intensity based absolute quantification (iBAQ) of identified proteins revealed a clear difference between MFGM-enriched whey and its controls including enrichment of known MFGM proteins and non-MFGM proteins that are enriched simultaneously, some of which have previously been demonstrated to display anti-viral activity. Although not completely absent from other whey protein preparations, MFGM-enriched whey had the highest specific and total phospholipid levels. Conclusion MFGM-enriched whey displayed antiviral activity against multiple viruses of clinical importance. This study provides insights into the active components in MFGM-enriched whey and may contribute to previous clinical observations with MFGM-enriched formula demonstrating reduced respiratory and gastrointestinal infections in formula fed infants.